2020
DOI: 10.3168/jds.2020-18296
|View full text |Cite
|
Sign up to set email alerts
|

MILK Symposium review: The importance of milk and dairy foods in the diets of infants, adolescents, pregnant women, adults, and the elderly

Abstract: The ongoing increase in life expectancy is not always accompanied by an increase in healthy life span. There is increasing evidence that dietary exposure in early life can substantially affect chronic disease risk in later life. Milk and dairy foods are important suppliers of a range of key nutrients, with some being particularly important at certain life stages. It is now recognized that milk protein can stimulate insulin-like growth factor-1 (IGF-1), essential for longitudinal bone growth and bone mass acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 123 publications
(132 reference statements)
0
47
0
5
Order By: Relevance
“…Several studies have reported that large consumption of sugar and sweet beverages among childhood worldwide exert negative health effects, [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127] but the effects on puberty onset are still controversial. Only one prospective study found an association between early sexual development and consumption of sugar-sweetened beverages in a sample of 5583 American girls.…”
Section: Macronutrient Intakementioning
confidence: 99%
“…Several studies have reported that large consumption of sugar and sweet beverages among childhood worldwide exert negative health effects, [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127] but the effects on puberty onset are still controversial. Only one prospective study found an association between early sexual development and consumption of sugar-sweetened beverages in a sample of 5583 American girls.…”
Section: Macronutrient Intakementioning
confidence: 99%
“…With an increase in the world population, milk consumption is expected to rise steadily over the next 50 years [ 2 ]. Meanwhile, people have become more aware of milk quality, which is mainly determined by the milk protein and fat content [ 3 , 4 ]. Therefore, intensifying milk production efficiency and quality has been a continued priority [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…And while not generally considered in FBDGs, many chronic diseases are diet-dependent and frequently begin in childhood, affecting quality of life and well-being throughout adolescence and adulthood. Adequate dairy intake in youth can beneficially impact health later in life [ 74 ], and adults who consume higher levels of dairy food, especially fermented dairy foods, may have a lower risk of several chronic diseases such as CVD, T2D, hypertension, and stroke [ 75 ].…”
Section: Dairy’s Essential Role In Child Health Within Sustainable Food Systemsmentioning
confidence: 99%